Remaining Life Assessment of Shell Course of Storage Tank 610-TK-104 Based on API Standard 653 at PT Kilang Pertamina Internasional RU II Dumai - Nazaruddin, Nazaruddin (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Riau, 2024)
This paper discusses about calculation of the remaining life of shell course storage tank 610 - TK - 104 based on API standard 653 PT Pertamina International Refinery unit II. The purpose of this research is to identify the reliability of the tank by knowing the minimum thickness, corrosion rate, and remaining life of the tank. Tank reliability analysis based on API 653 is carried out so that the tank continues to be in a safe condition and can continue to operate, so that failures in the tank can be avoided. The tank is made of ASTM A283 Grade C material. The tank has a diameter and height of 95.374 ft and 53.90 ft. The service accommodated is Crude Oil and Specific Gravity 0.860. The tank is protected from Internal Film Thin Coating material. The research methods used include visual inspection, data collection and information related to tank specifications, reliability analysis of the tank. Based on the calculation, the remaining life of the tank obtained is in an unacceptable condition because it is < 10 years, so the solution that can be done is to reduce the maximum liquid level of the tank by 14.06 ft so that the tank can withstand pressure for a long time